Exploring instructional leadership practices of principals in selected nursing and midwifery colleges under Christian Health Association of Malawi - Master Phiri, Liviness (2021)
Instructional leadership is crucial to the success of colleges since it creates a climate that is conducive to teaching and learning. However, there is a dearth of literature from developing countries including Malawi. On the other hand, the job description of CHAM college principals directly captures instructional leadership attributes. However, it is not known whether CHAM college principals practice instructional leadership as stipulated in their job description and from literature. This study explored instructional leadership practices of principals in selected Christian Health Association of Malawi (CHAM) nursing and midwifery colleges using Hallinger and Wang instructional leadership model. Qualitative research approach was used. Data were collected from 6 principals through individual in depth interviews. The participants consisted of four males and two females. Three particiapnts had served as principals for less than 2 years and the other three had served as college principals for 3 to 4 years. The data were analyzed using thematic template analysis. The study findings showed that principals in the study try to implement some instructional leadership practices in line with the model developed by Hallinger and Wang. However, principals are not able to monitor instructional program. The study also revealed that most of the principals lacked resources and experienced increased workload which hindered their implementation of instructional leadership activities. Therefore, necessary measures should be taken so that college principals can focus on the instructional leadership activities according to Hallinger and Wang (2015) model aimed at improving student learning in colleges.